THE INFLUENCE OF PARTICIPATORY LEADERSHIP STYLE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A VARIABLE INTERVENING AT PT RAHAYU PERDANA TRANS - Ilmil Fazri, Darul; Ahmad Badawi saluy; Abdul Bari; Novawiguna Kemalasari (Dinasti International Journal of Digital Business Management, 2022)
This study aims to identify and analyze the effect of participatory leadership style and organizational commitment on employee performance with job satisfaction as an intervention variable at PT Rahayu Perdana Trans. The instrument used in this research is a questionnaire to 150 respondents which is then analyzed descriptively and quantitatively. Descriptive analysis in this study is used to provide an overview of the characteristics of respondents and an overview of research variables, while quantitative analysis conducted by SEM-PLS (Partial Least Square) will be used to test the hypothesis in this study. Based on the results of the analysis in this study, it can be seen that participatory leadership style has a positive and significant effect on job satisfaction, organizational commitment has a positive and significant effect on job satisfaction, participatory leadership style has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on performance. employees, job satisfaction has a positive and significant effect on employee performance, participatory leadership style and organizational commitment have a positive and significant effect on job satisfaction, and participatory leadership style and organizational commitment have a positive and significant effect on employee performance.